Impact of mediterranean diet adherence on periodontal disease: A systematic review and meta-analysis - Hussam M. Alqahtani; Nawaf Alfahad; Sohaib Shujaat; Abdullah Alghamdi; Amal Alamri; Saleh Alwatban (Saudi Journal of Oral Sciences)
Periodontal disease is a bacterial-driven inflammatory condition compromising the supporting anatomical structures of teeth and can result in tooth loss. The Mediterranean diet (MD), which emphasizes the consumption of healthy fats, fruits, vegetables, and whole grains, is thought to benefit periodontal health. This systematic review examines the evidence regarding the connection between MD adherence and periodontal disease-related outcomes. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, this systematic review was registered with PROSPERO Comprehensive searches of SCOPUS, MEDLINE, The Cochrane Library, and Web of Science identified 15 eligible articles. Data extraction included study characteristics, intervention details, sample sizes, and outcomes related to periodontal health. The bias risk assessment was conducted using the Newcastle–Ottawa Scale in cohort, cross-sectional, and prospective/exploratory studies. In contrast, randomized controlled trials (RCTs) underwent evaluation utilizing the Cochrane risk of bias (RoB) tool – a meta-analysis employed a random-effects approach to accommodate the variability in treatment effect estimates among the included papers. The meta-analysis revealed that adherence to the MD significantly prevented low, moderate, and severe periodontal disease (Tau² =5.31, χ2 = 43804.00, P < 0.00001). Subgroup analyses demonstrated considerable reductions in gingival inflammation, with a standardized mean difference (SMD) of − 1.46, a 95% confidence interval of − 2.07 to − 0.09, and a P = 0.03, as well as reductions in bleeding on probing (P = 0.0001) among MD adherents. RoB assessments indicated good quality in two out of ten cross-sectional studies, with minimal bias in RCTs; however, one RCT presented with unclear risks. MD adherence is linked with decreased periodontal parameters, including gingival inflammation and plaque levels. These findings suggest that incorporating the MD into dietary recommendations may function as a beneficial adjunctive strategy in avoiding and controlling periodontal disease. Further research, particularly RCTs, is warranted to reinforce these associations.